Perfil dos servidores da Universidade Federal do Espírito Santo com empréstimo consignado - Ribeiro, Anneliza Baptista (2014)
The credit consigned is defined as a type of loan whose value of the monthly installment is deducted in the salary of the debtor. With a high level of adhesion in the past years, is the most common kind of access to credit used by public servants because of the low interest rate, among other attractives, which contributes to expose to risk their income. To accomplish the main goal of identifying if characteristics of demographic profile of the servants in activity at Federal University of Espírito Santo (UFES) are connected with the commitment of their incomes to consignedloans a research with quantitative approach was elaborated using personal and financial data of the servants in the year 2013 obtained from the institution’s database and through a survey which totalized 210 valid responses. All the informations were analyzed using statistical’sresources, like descriptives analysis of the data, table of contingencies with chi-square interpretation and logistic regression. The results show that the variables education, income, number of dependent and gender are associated with the increase of the commitment of income with consigned loan and that, even though men appear as the gender that most chooses this kind of loan, they commit least of their income with it, when compared to women. Females and those with lower levels of education and income are more likely to commit a bigger percentage of their wage withdiscounted loan on leaf. Ultimately, even though the results show that only the lack of financial education does not explain the high level of involvement of their wage with loans, many respondents said they did not master the subject and find it difficult to manage their own personal finances. Thus, the intervention’s plan proposed on the beginning and described in the end of the research suggests that the institution needs to invest in the financial education of servers; provide psychological support to over-indebted and forbid initiatives that stimulate consumption at the workplace